2002
DOI: 10.1002/eej.10016
|View full text |Cite
|
Sign up to set email alerts
|

In situ observation of the initial adsorption process of layer‐by‐layer sequential adsorbed polyelectrolyte film using an AFM

Abstract: SUMMARYIn this study, we demonstrate the first observation results of the initial adsorption processes of polyelectrolytes to the substrate in solution by in situ observation using an AFM. The adsorption form of polyelectrolytes was changed by solution pH. It was found that the surface structure was controlled by adsorbing time of polyelectrolytes and strongly affected by both the previously formed under layer and the solution pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Yoo et al [15] and Shiratori et al [14] carried out similar studies on the effect of pH on the thickness of PAA/PAH polymeric films. The results obtained in the present study agree reasonably with values reported in the literature [14,15,28]. The cause of the increase in thickness in the pH regime from 2.5 to 4.5 is mainly due to the linear charge density of the adsorbing polymer chains and the surface charge density prior to every adsorbing step.…”
Section: Resultssupporting
confidence: 94%
“…Yoo et al [15] and Shiratori et al [14] carried out similar studies on the effect of pH on the thickness of PAA/PAH polymeric films. The results obtained in the present study agree reasonably with values reported in the literature [14,15,28]. The cause of the increase in thickness in the pH regime from 2.5 to 4.5 is mainly due to the linear charge density of the adsorbing polymer chains and the surface charge density prior to every adsorbing step.…”
Section: Resultssupporting
confidence: 94%
“…Exposing a surface alternatively to cationic and anionic polyelectrolytes causes multilayer buildup on the surface with each layer with thickness around 3-4 nm [27], [28]. This assembly process is called electrostatic layer by layer assembly.…”
Section: Layer By Layer Assembly Of Polyelectrolytementioning
confidence: 99%
“…Secondary non-electrostatic forces, such as hydrogen-bonding or hydrophobic interactions [8][9][10][11][12], may also influence the film formation. Atomic force microscopy, AFM, has been used increasingly to provide information on the outer surfaces of LbL films [13][14][15][16][17][18]. Moreover, investigations of the adsorption of single polyelectrolyte molecules is helping to elucidate the different phases of organization of the polyion layers and their changes in conformation (coil-to-globule) in a controlled environment [19][20][21].…”
Section: Introductionmentioning
confidence: 99%